Beginning Database Design - Churcher, Clare (Apress, 2012)
Everyone keeps data. Big organizations spend millions to look after their payroll, customer, and transaction data. The penalties for getting it wrong are severe: businesses may collapse, shareholders and customers lose money, and for many organizations (airlines, health boards, energy companies), it is not exaggerating to say that even personal safety may be put at risk. And then there are the lawsuits. The problems in successfully designing, installing, and maintaining such large databases are the subject of numerous books on data management and software engineering. However, many small databases can be found within these large organizations and also in small businesses, clubs, and private concerns. When these go wrong, it doesn’t make the front page of the papers, but the costs, often hidden, can be just as serious.